2005
DOI: 10.1016/j.virol.2004.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Cell wall localization of Red clover necrotic mosaic virus movement protein is required for cell-to-cell movement

Abstract: The Red clover necrotic mosaic virus movement protein (MP) is essential for cell-to-cell movement. Eight previously characterized alanine-scanning mutants of the MP were fused to the green fluorescent protein (GFP) and expressed from viral infectious transcripts. Inoculated plants were assayed for movement and intracellular accumulation of MP by confocal laser-scanning microscopy. A strict correlation was observed between the targeting to the cell wall (presumably the plasmodesmata) and cell-to-cell movement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…It was found that the three mutants identified in this current study that suppress RNA silencing also localized to the cell wall. Alanine substitutions around amino acids 27 and 277 both consistently localized to the cell wall in those studies while 122 localized to the cell wall approximately 10% of the time (Tremblay et al, 2005). Of the three MP alanine mutants that did not suppress silencing in this current study, mutants 128 and 161 exhibited no localization to the cell wall in the previous study, while mutant 144 did.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…It was found that the three mutants identified in this current study that suppress RNA silencing also localized to the cell wall. Alanine substitutions around amino acids 27 and 277 both consistently localized to the cell wall in those studies while 122 localized to the cell wall approximately 10% of the time (Tremblay et al, 2005). Of the three MP alanine mutants that did not suppress silencing in this current study, mutants 128 and 161 exhibited no localization to the cell wall in the previous study, while mutant 144 did.…”
Section: Discussionmentioning
confidence: 87%
“…MP might instead work intercellularly to disrupt the RNA silencing cascade by disrupting the spread of the silencing signal. MP is known to target to the cell wall of plant cells, presumably the plasmodesmata, a logical location for the interception of the spreading signal adding support for this argument (Osman and Buck, 1991; Tremblay et al, 2005). Indeed, earlier work in characterizing the MP alanine-scanning mutants used in these studies suggests that the intracellular location of MP directly correlates with the ability of MP to suppress RNA silencing.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In the CP-independent mechanism, MP alone mediates cell-to-cell movement by modifying the size exclusion limits of the plasmodesmata and transporting themselves and viral genomic RNA as ribonucleoprotein complexes. The cell-to-cell movement process of members of the tobamovirus and dianthovirus genera are CP-independent [2,9] whereas that of members of the genera Comovirus, Closterovirus, Cucumovirus, Bromovirus, Nepovirus, Potyvirus and Potexviruses is CPdependent [1,5,8,10,11]. In addition to MP and CP, in some viruses replicase genes are implicated in local and systemic infection [1,12,13].…”
Section: Introductionmentioning
confidence: 99%